Kesamaan dan Kualitas Persahabatan Pada Mahasiswa - Liddiniyah, Alfaiqoh; Maryam, Effy Wardati (Personifikasi: Jurnal Ilmu Psikologi, 2023)
Based on a survey with several students, it shows students had a conflict, debate, disputes, feelings of annoyance, so that they cannot solve problems with friends. The existence of conflict will have an impact on the quality of friendship. This study aims to determine the relationship between similarity and the quality of friendship in students of Muhammadiyah University of Sidoarjo. This study uses a quantitative research method with a correlational approach and uses a scale measuring instrument, namely the similarity scale and the friendship quality scale. The sample in this study was 336 students from a population of 9591 students who were taken using incidental sampling technique. Data analysis was performed using the Pearson product moment correlation. The results of data analysis show the correlation coefficient value of 0.358 with a significance of 0.000 smaller than 0.05, meaning that there is a positive and significant relationship between similarity and friendship quality, the higher the similarity students have, the higher the friendship quality students have. On the other hand, the lower the similarity that students have, the lower the quality of friendship they have. The effective contribution of the similarity variable is 12.8% to the quality of friendship. While the remaining 87.2% is influenced by other factors.